Effects of Different Monochromatic Light Combinations on Cecal Microbiota Composition and Cecal Tonsil T Lymphocyte Proliferation - Zhang, Yijia; Wang, Zixu; Dong, Yulan; Cao, Jing; Chen, Yaoxing (Frontiers in Immunology, 2022)
Emerging data demonstrated that the gut microbiota plays an important role in protecting the integrity of the epithelial barrier, forming mucosal immune system, and maintaining intestinal homeostasis through its metabolites. However, the intestinal microbiota community can be affected by environmental factors, such as litter, photoperiod, or temperature. Thus, we investigated the effect of different monochromatic lights combination on cecal microbiota composition, as well as, explored the molecular mechanism by how the external light color information mediate cecal tonsil T lymphocyte proliferation. In this study, a total of 160 chicks were exposed to monochromatic light (red (R), green (G), blue (B), or white (W) light) or green and blue monochromatic light combination (G→B) from P0 to P42. 16S rRNA microbial sequencing results showed that the richness and diversity of the cecum microbiota and the abundance of Faecalibacterium, Butyricicoccus was significantly increased in the G→B. With consistency in the upregulation antioxidant enzyme ability and down-regulation pro-inflammation levels in the cecum, we observed an increases in the number of goblet cells, sIgA+ cells, tight junction protein (Occludin, ZO-1, Claudin-1) and MUC-2 expression in the cecum of the G→B. Metabolomics analysis revealed that the relative abundance of metabolites related to butyrate were significantly increased in G→B. In vitro experiment, we found butyrate could effectively induce T lymphocyte proliferation and cyclinD1 protein expression. However, these butyrate responses were abrogated by HDAC3 agonists, STAT3 antagonists, or mTOR antagonists, but were mimicked by GPR43 agonists or HDAC3 antagonists. Thus, we suggested that G→B can indirectly affect the composition of cecal microbiota, increase relative abundance of Faecalibacterium, Butyricicoccus and butyrate production by reducing the level of oxidative stress in the cecum. Exogenous butyrate could promote T-lymphocyte proliferation of cecal tonsil by activating the GPR43/ HDAC3/p-STAT3/mTOR pathways.